A case of vestibular schwannoma mimicking burning mouth syndrome - Suga, Takayuki (Biopsychosoc Med, 2021)
BACKGROUND: An oral burning sensation with unidentified cause in patients with preexisting psychosocial conditions is usually diagnosed as burning mouth syndrome. However, unexpected organic lesions may be detected in rare cases. CASE PRESENTATION: A 35-year-old woman had chief complaints of a burning sensation and numbness of the right side of the lip and tongue, as well as a dry sensation of the mouth with a taste disturbance of the right side of the tongue. The symptoms were continuous and did not show any daily fluctuations. The symptoms started without any recognizable triggering factor six months before her first visit to our clinic,. No abnormality was detected in her mouth. MRI images revealed an approximately 30 × 30 mm well-defined mass localized in the right cerebropontine angle compressing the trigeminal nerve, which was diagnosed as schwannoma of the right auditory nerve. CONCLUSIONS: It is important for clinicians to consider the possibility of brain tumors in their differential diagnosis of BMS. Although it is not always easy to eliminate all diseases that may cause an oral burning sensation in patients with BMS-like symptoms, more attention and careful examination based on the patient’s psychosomatic background features and other possible causes are needed to rule out organic diseases.